Lestaurtinib as a FLT3 inhibitor (Hematology Meeting Reports, 2009)
Overexpression of the FLT-3 receptor is common in Acute Myeloid Leukaemia (AML) and mutations represent one of the commonest mutations which occur in approximately 30% of adult cases, although less frequent in older patients. The most frequently detected mutation is an Internal Tandem Duplication (ITD) in the juxtamembrane position of the receptor (24%), and a point mutation in the activation loop usually at positive 385 (7%). The mutations are in frame and constitutively activate via STAT5. Mutations are unevenly distributed in FAB and cytogenetic groups. They have highest frequency in Acute Promyelocytic Leukaemia (35-40%), and are associated with a normal karyotypic or trisomy 8. They are less frequent in poor risk karyotypes or in core binding leukaemias. The association with normal karytyope has the additional interest of being associated with mutations of the nucleophosmin 1 mutation in approximately two-thirds of cases. Whether these mutations are themselves leukaemogenic is thought to be unlikely.